PENGEMBANGAN MEDIA GAME MONOPOLI BARUANG BERBASIS AUGMENTED REALITY (AR) PADA MATERI BANGUN RUANG KELAS V SEKOLAH DASAR - Syafa'ah, Umi; Eka Subekti, Ervina; Cahyadi, Fajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop monopoly learning media based on Augmented Reality, material for building classrooms in elementary schools. The aim of this research is to find out the feasibility of monopoly learning media based on Augmented Reality, building material for classrooms in elementary schools. The type of this research is Research & Development (R&D) with using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research was carried out at SD N 02 Sumur in Brangsong sub-district, Kendal Regency. subject The research was class V of SD N 02 Sumur as a test subject with a total of 18 students as respondents. The data collection technique in this research used interviews and questionnaires, while the data analysis technique was qualitative descriptive and quantitative descriptive. The validation results from material experts obtained a percentage of 93.7% and the validation results from media experts obtained 94.6%. The results of the teacher response questionnaire assessment obtained a percentage of 95.7% and the results of the student response questionnaire assessment obtained a percentage of 91.9%. Meanwhile, 8.0% still felt they did not understand the media. However, from the percentage results above, the augmented reality-based Monopoly Game learning media is